Prevalence of caries and developmental defects of enamel in 9-10 year old children living in areas in Brazil differing water fluoride histories - Dini, E. L.; Holt, R. D.; Bedi, R. (Nature Publishing Group, 2000)
Aims To assess the prevalences of caries, of developmental defects of enamel and their interrelationship in Brazilian 9-10-year-olds from areas of contrasting fluoridation histories.Methods systematic random sampling procedures were used to select children from an area where water had been fluoridated in 1963 and from a second area where water had been fluoridated since 1998. Clinical examinations for caries were carried out using the DMFT index and WHO diagnostic criteria. Developmental defects of enamel on upper incisors were diagnosed using the DDE index.Results A difference of 40% in DMFT was observed, with a lower prevalence of disease in the area fluoridated since 1963. Diffuse opacities affected 14.3% of the children from the area fluoridated since 1963 compared with only 2.4% in the area fluoridated in 1998. Children living in the area fluoridated in 1963 who had diffuse defects had twice the chance of being free from caries compared with those living in the same area who had no defects or who had only demarcated or hypoplastic defects.Conclusions This study confirms previous ones in showing the benefits of water fluoridation. Diffuse opacities of upper incisors affected relatively few subjects in either of the two areas.